Experimental and numerical analysis of airflow around a building model with an array of domes. (February 2021) - Tavakol, Mohammad Mehdi; Yaghoubi, Mahmood; Ahmadi, Goodarz
Abstract: Domed and curved structures are widely used in the hot arid regions of Iran and other Middle Eastern countries because of their ventilation advantages. Many experimental and numerical studies were reported for the wind flow over a single dome or single vault. However, studies of the airflow around an array of domes, which are important for designing or constructing these structures, are scarce. In this study, the wind flow around a building model with an array of domes was studied experimentally and numerically. A hot-film anemometer was used, and airflow velocity profiles around the building model in a wind tunnel were measured. The RANS approach and the large eddy simulation (LES) were used, and simulations were performed for Reynolds numbers of 43, 000 and 430, 000. The predicted streamwise mean velocity and root-mean-square fluctuation velocity profiles around the model were compared with the wind tunnel data, and good agreements were observed. The presented results indicated that the separation points over the domes move further downstream for the second and third domes compared with the first dome. Also, the peak suction pressure was observed over the first dome near the dome apex, and the maximum pressure was seen in the windward side of the third dome. The results were compared with the case of airflow around a single dome, and the influence of the dome's location in the array was discussed. Also, recommendations for the design or construction of buildings with an array of domes were provided. Highlights: Flow field around a building model covered by an array of domed roofs was studied numerically and experimentally. Experiments were undertaken using the hot-film probe in an artificially generated atmospheric boundary layer profile. Numerical simulations were accomplished with Large Eddy Simulation (LES) using proper SGS model. Influence of various grid resolutions for LES were evaluated and discussed. Influence of flow Reynolds number as well as aerodynamic interference of domes was discussed.